Cr3+ Activated Garnet Phosphor with Efficient Blue to Far‐Red Conversion for pc‐LED. Issue 20 (8th August 2021) - Xiao, Han; Zhang, Jingnan; Zhang, Liangliang; Wu, Hao; Wu, Huajun; Pan, Guohui; Liu, Feng; Zhang, Jiahua
Abstract: Far‐red (FR) phosphor‐converted light‐emitting diodes (pc‐LEDs) driven by blue LED chips are novel light sources for applications in phototherapy, photosynthesis, natural light simulation, and so on but still bear low electricity‐to‐FR light conversion efficiency (≤ 23%) due to deficiency of phosphors that have both high blue light absorptance and high FR internal quantum efficiency (IQE) for the realization of efficient blue to FR conversion. FR Ca3 Sc2 Si3 O12 (CSSG):Cr 3+ garnet phosphor has ultra‐high IQE (> 90%) but low blue light absorption. Here, a twofold increase of blue light absorption cross‐section is reported with still high FR IQE via Lu 3+ −Mg 2+ substitution for Ca 2+ −Sc 3+ in CSSG:Cr 3+ to form Ca3– x Lu x Mg x Sc2– x Si3 O12 :Cr 3+ garnet solid solution, which is attributed to enhanced mixing of odd‐parity configuration into 3 d configuration of Cr 3+ induced by the cations substitution. Optical properties, crystal field strengths, and thermal stabilities of the solid solution phosphors are studied as a function of x . After complete replacement of Sc 3+, the as‐fabricated FR pc‐LED emits at 750 nm with 65.7% blue‐to‐FR quantum conversion efficiency and consequently offers an electricity‐to‐FR light conversion efficiency over 30%. Moreover, the solid solution phosphors show high quenching temperatures in the range of 580–610 K. The results can advance the development of efficient FR phosphors and pc‐LEDs for various applications. Abstract : Ca3– x Lu x Mg x Sc2– x Si3 O12 :Cr 3+ garnet solid solution shows both high blue light absorptance and high far‐red (FR) internal quantum efficiency for the realization of efficient blue to FR conversion. With CaLu2 Mg2 Si3 O12 :Cr 3+, the FR phosphor‐converted light‐emitting diode (pc‐LED) emits at 750 nm with 65.7% blue‐to‐FR quantum conversion efficiency and offers an electricity‐to‐FR light conversion efficiency over 30%. It can advance the development of efficient FR phosphors and pc‐LEDs for various applications.